In‐Situ and Triple Oxygen Isotope Characterization of Seafloor Drilled Cherts: Marine Diagenesis and Its Bearing on Seawater Reconstructions. (25th February 2023) - Zakharov, David O.; Marin‐Carbonne, Johanna; Pack, Andreas; Di Rocco, Tommaso; Robyr, Martin; Vennemann, Torsten
Abstract: Cherts are used to reconstruct the evolution of seawater δ 18 O and temperature over geological time. However, given the influence of marine diagenesis, reconstructing seawater from the isotope composition of cherts is not straightforward, resulting in ambiguity of interpretation. Here, we present a detailed isotope and petrographic investigation of deep‐sea drilled 135–40 Ma cherts with focus on the effects of marine diagenesis. We combined triple O‐isotope data with in‐situ δ′ 18 O‐ 16 OH/ 16 O measurements using secondary ion mass spectrometry (SIMS). We also provide electron microprobe maps, traditional δ′ 18 O measurements from petrographically diverse domains, and δD and H2 O wt.% values. The bulk δ′ 18 O values range between 29‰ and 38‰ in our collection, while SIMS δ′ 18 O data reveal significant intra‐sample heterogeneities up to 6‰ related to distinct petrographic features (e.g., filled radiolarian tests) and to micrometer‐scale variations in silica forms. Further, the δ′ 18 O—Δ′ 17 O values of these seafloor‐drilled cherts plot near and under equilibrium curve. Both triple‐O and SIMS δ′ 18 O results reflect diagenesis in presence of marine pore waters at temperatures higher than ambient seawater, which is especially appreciable in cherts deposited on young oceanic crust. Despite the relatively constant δ 18 O seawater values over last 135 Ma, the marine silica spanning between 0 and 135 Ma occupies a wide compositional space in the δ′ 18 O—Δ′ 17 O rather than an equilibrium curve. The δ′ 18 O values of cherts from modern‐seafloor positively correlate with the oceanic crustal age at the time of deposition, hinting at the importance of the heat flux in the diagenetic recrystallization of marine silica. Plain Language Summary: Chemical sediments extracted from seafloor represent an archive of ocean temperatures and solutes. Chemical resilience of siliceous sediments with composition of >90 wt.% SiO2 presents a promising avenue to constrain temperature of ancient oceans from distant geological epochs. However, such rocks termed cherts undergo complex recrystallization during compaction and lithification below the seafloor, preventing direct measurements of ocean temperatures. To isolate the effect of diagenesis, we carefully investigated several Mesozoic and Cenozoic seafloor‐drilled cherts. We used oxygen isotope ratios as a common proxy for temperature to test for the effects of recrystallization of these cherts that were buried at depths between 80 and 960 m. We combined two state‐of‐the‐art types of isotope measurements: (a) non‐destructive in‐situ measurements from microscopic domains and (b) bulk high‐precision triple O‐isotope ratios. We observe complex mineralogical and isotope compositions on the scale of 10–100 μm. The triple O‐isotope ratios depict the combined effects of original precipitation from seawater column and the thermal regime of recrystallization in subseafloor conditions. The compiled O‐isotope ratios of silica extracted from seafloor correlates with the age of oceanic crust. Since the age of oceanic crust and the heat flux are related, these observations hint at the importance of the sediment geothermal evolution during diagenesis. Key Points: Mesozoic and Cenozoic seafloor‐drilled cherts were measured for triple O‐isotope and in situ secondary ion mass spectrometry δ′ 18 O‐ 16 OH/ 16 O values In situ measurements display up to 6‰ range in the δ′ 18 O values of seafloor‐drilled cherts The δ′ 18 O‐Δ′ 17 O values of cherts plot near and under the silica‐seawater equilibrium curve (20°C–40°C). Together with the in‐situ variability, these data are best explained by a combination of original precipitation and recrystallization in sub‐seafloor conditions